Modulation of Motor Cortex Activity After Intrathecal Baclofen Delivery in Chronic Thoracic Spinal Cord Injury - Štětkářová, Ivana; Keller, Jiří (Frontiers in Neurology, 2022)
Objectives Intrathecal baclofen (ITB) is commonly used for reduction of spasticity in chronic spinal cord injury (SCI). Its clinical effect is well-known; however, exact mechanisms of long-term effect of continuous ITB administration (cITBa) on modulation of cortical processes have not been elucidated. The aim of this study was to evaluate changes in motor cortex activation for healthy upper limbs in comparison to impaired lower limbs by functional magnetic resonance imaging (fMRI). Methods Ten subjects (eight males, 20–69 years) with thoracic SCI presenting no voluntary movements of lower limbs (except one) were enrolled in the fMRI study. fMRI at 1.5T with a finger tapping paradigm and mental movement simulating foot flexion on the dominant side were performed before, 3 months, and 1 year after start of cITBa. fMRI data processing was carried out using FMRI Expert Analysis Tool (FEAT), part of FSL. A second-level analysis was carried out using FLAME stages 1 and 2. The level of spasticity was assessed with the Modified Ashworth scale (MAS). Results Continuous ITB significantly decreased limb spasticity in all the subjects (group MAS spasticity dropped from 3 to 0.3). The second-level analysis (Z > 1.6, cluster significance threshold p =0.05) revealed increased activation of the primary sensorimotor cortex of the foot between baseline and 3 months, and 3 months and 1 year. Conclusion Increased sensorimotor cortex activation with spasticity reduction after cITBa may reflect distant functional reorganization because of long-term mediated neuroplastic changes in the sensorimotor cortex. Better understanding of modulation of brain function in SCI after cITBa may influence the field of neurorehabilitation.